POTENTIAL IMPACT OF CLIMATE CHANGE ON POTATO LATE BLIGHT OUTBREAK IN WESTERN UTTAR PRADESH AND PUNJAB USING JHULSACAST MODEL - Dua, Vijay Kumar; Singh, B P; Ahmad, Islam; Sharma, Sanjeev (Potato Journal, 2016)
Potential impact of climate change in potato seed crop due to late blight appearance and number of chemical sprays required to control it in Punjab and western Uttar Pradesh are analysed in this study using JHULSACAST. The model was run using districts level data on minimum and maximum temperature (ºC) of Indian Meteorological Department’s normals (years 1971 to 2000) for baseline (year 2000) and future climate scenarios (years 2020 and 2055) for 13 districts of Punjab and 21 districts of western Uttar Pradesh. Hourly temperature(ºC) data required for JHULSACAST was derived from minimum and maximum temperature (ºC). Kriging method was used to interpolate data over geographical area of districts. Under the favourable relative humidity in Punjab, the model predicted earliest late blight appearance is during 13th to 25th October in baseline scenario (2000) which is expected to be delayed by 0 to 6 days in 2020 and 12 to 14 days in 2055 scenarios. In western Uttar Pradesh, earliest late blight appearance during the potato crop season was predicted during 13th October to 1st November in baseline year 2000 and is expected to be delayed by 0 to 8 days in 2020 and 10-21 days in 2055. The change in date of late blight appearance and its delay in years 2020 and 2055 is due to expected increase in temperature by 1.08 and 2.98 ºC respectively over the baseline year 2000. In Punjab, there were average 105 late blight favourable days out of 182 suitable potato growth days in year 2000; the number is likely to be increased to 135 and 140 days in 2020 and 2055 respectively in Punjab. In western Uttar Pradesh, potato growing season was warmer which would decrease late blight favorable days by 7 and 27 in 2020 and 2055, respectively. The number of sprays required to control late blight in potato seed crop would be 7.3 and 8 in future scenario (2020 and 2055) in comparison to 6.5 in baseline (2000) in Punjab. In contrast, there would be no change in number of sprays in year 2020 (over baseline year 2000) in western Uttar Pradesh, however, due to further increase in temperature in year 2055, it could be reduced by 2.